Stakeholder Collaboration Strategy in the Development of Gegesik Kulon Tourism Village: A MACTOR Analysis - Irma Suryahani; Dicky Satria Ramadhan; Suharno Suharno (Universitas Muhammadiyah Ponorogo, 2025)
This study explores the development strategy of Gegesik Kulon, a potential tourism village in Cirebon that uniquely combines travel with cultural preservation. However, it faces challenges such as suboptimal tourism management and low carrying capacity among stakeholders. Additionally, this area has the highest poverty rate in Cirebon Regency. By utilizing the MACTOR method, this study identifies the involvement of stakeholders in the development process of the Gegesik Kulon Tourism Village. Through purposive sampling based on the Quadruple Helix concept, the study highlights the importance of collaboration among academics, local governments, tourists, and business actors. The results indicate that the main actors include Kuwu Gegesik Kulon, the Tourism Awareness Group, the Cirebon Regency Culture and Tourism Office, and academics, all of whom play a crucial role in the development of village tourism. These findings advocate for a development strategy that emphasizes stakeholder integration to promote sustainable tourism, ultimately aiming to enhance the economic viability and integrity of Gegesik Kulon's cultural tourism.